Near Ring Multiplications on a Modified Near Module Over a Near Ring (European Journal of Pure and Applied Mathematics, 2021)
We introduce the notion of a modied near module M over a near ring N and explain a method of obtaining near ring multiplications via a special type ofÂ maps from M into N called semilinear maps.